2006
DOI: 10.1016/j.chemosphere.2006.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of some environmentally relevant factors on the availability of bisphenol A with negligible-depletion SPME

Abstract: The effect of some environmentally relevant factors including salinity, pH, and humic acids on the availability of bisphenol A (BPA) was evaluated by using the negligible-depletion solid-phase microextraction (nd-SPME) biomimetic method. With the variation of salinity (0-500 mM NaCl) and pH (5.0-8.5) of aqueous solutions, the partition coefficients of BPA between the nd-SPME fiber and the aqueous solution varied in the range of log D = 3.55-3.86, which indicates that the salinity and pH can influence the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…There are procedural differences between the two studies that may explain some, but not all, of the discrepant findings. First, in the Doerge study, DMSO was used as a solvent and water as the vehicle for BPA delivery as opposed to EtOH as solvent and oil as vehicle in the present study and BPA release and absorption can differ with these variables [36, 37]. It is possible that relative to an oil depot, BPA is more rapidly released from water resulting in different absorption kinetics, particularly with the s.c. route which would explain the extreme peak after s.c. injection in the Doerge study.…”
Section: 4 Discussionmentioning
confidence: 99%
“…There are procedural differences between the two studies that may explain some, but not all, of the discrepant findings. First, in the Doerge study, DMSO was used as a solvent and water as the vehicle for BPA delivery as opposed to EtOH as solvent and oil as vehicle in the present study and BPA release and absorption can differ with these variables [36, 37]. It is possible that relative to an oil depot, BPA is more rapidly released from water resulting in different absorption kinetics, particularly with the s.c. route which would explain the extreme peak after s.c. injection in the Doerge study.…”
Section: 4 Discussionmentioning
confidence: 99%
“…The effects of CNMs on the uptake of a compound might thus be better explained via the C free that can be measured with negligible depletion solid-phase microextraction (nd-SPME) (Mayer et al, 2000a,b;Hu et al, 2006;Yang et al, 2008). The C free of polycyclic aromatic hydrocarbons (PAHs) in nC 60 suspensions was measured in our previous study (Hu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This slight enhancement of C free with DOC concentration, however, should not be neglected. This phenomenon also was observed for other polar compounds, such as dinitrophenolic compounds [32], bisphenol A [33], and alkylphenols [17]. Biological exposure experiments indicated that statistically, the bioavailability of ATR was not affected by the DOM [28,29], but enhanced uptake by Daphnia magna was observed in cases with low DOC concentrations [28].…”
Section: Resultsmentioning
confidence: 78%